Relationship Development in Construction Partner Selection - Davis, Peter (RICS Foundation, 2004)
Relationships between actors in organizations are incrementally refined evolving strategies that change the context in which partner organizations act. The development of relationships is an iterative and evolutionary learning process that has many implicit characteristics. Three important characteristics are commitment, trust and cooperation. These become increasingly active or sometimes latent throughout the relationship development process. Relationship development encompasses partner selection, when the purpose of the relationship is defined, boundaries establishment and finally value creation and maintenance. These stages are the learning phases of the relationship contract and represent the incubator of the characteristics mentioned earlier. Relationship contracting is described using significant research investigating marketing and its transition to relationship marketing. A relationship development process is explored in this environment. Three recent public sector projects are set out as exemplars where relationship development theory is seen to be in operation in a construction context. These case studies anchor the relationship marketing theory into construction practice. The implications of relationship marketing for construction include forging stronger ties that encompass technical knowledge and learning and affect the social capital of the industry. Evidence from the example projects, illustrates how relationship development process can deliver advantages to stakeholders in the supply chain.